Cardiac tamponade and heart failure secondary to ventriculo-pleural shunt malfunction: a rare presentation. (25th January 2011) - Zaman, M; Akram, H; Haliasos, N; Bavetta, S
Abstract : We report an unusual case of a patient with a ventriculo-pleural shunt presenting with signs and symptoms of heart failure due to massive pericardial effusion. Imaging revealed the distal shunt catheter end within the middle mediastinum to have migrated from the pleural space. The patient underwent a shunt revision procedure resulting in complete resolution of the presenting pathology. We intend to draw the reader's attention to this rare presentation of ventriculo-pleural shunt malfunction.